Impact of breastfeeding and other early-life factors on the development of the oral microbiome - Arishi, Roaa A.; Lai, Ching T.; Geddes, Donna T.; Stinson, Lisa F. (Frontiers in Microbiology, 2023)
The oral cavity is home to the second most diverse microbiome in the human body. This community contributes to both oral and systemic health. Acquisition and development of the oral microbiome is a dynamic process that occurs over early life; however, data regarding longitudinal assembly of the infant oral microbiome is scarce. While numerous factors have been associated with the composition of the infant oral microbiome, early feeding practices (breastfeeding and the introduction of solids) appear to be the strongest determinants of the infant oral microbiome. In the present review, we draw together data on the maternal, infant, and environmental factors linked to the composition of the infant oral microbiome, with a focus on early nutrition. Given evidence that breastfeeding powerfully shapes the infant oral microbiome, the review explores potential mechanisms through which human milk components, including microbes, metabolites, oligosaccharides, and antimicrobial proteins, may interact with and shape the infant oral microbiome. Infancy is a unique period for the oral microbiome. By enhancing our understanding of oral microbiome assembly in early life, we may better support both oral and systemic health throughout the lifespan.A search was performed in PubMed, Web of science, Scopus, Google Scholar, ProQuest and One Search (English) with the following combinations of search terms: "infant / toddler / early life / temporal development" with "oral / saliva / buccal / salivary / plaque / mouth" and "microbiome / microbiota / bacteria". The search covers the prior to August 2023.Early-life is a curical window of time for eastablishment and devlopment of the oral microbiome. To date, there are relatively few studies examining temporal development of the oral microbiome, and those that do exist largely include low numbers of participants (< 300).Compared to the infant gut microbiome, the composition and development of the oral microbiome has received little attention, resulting in a poor understanding of this important environment. Current evidence suggests that similar to the adult oral microbiome, the infant oral microbiome is dominated by Streptococcus (